CO2 partial pressure and fluxes in the Amazon River plume using in situ and remote sensing data. (15th February 2021) - Valerio, Aline M.; Kampel, Milton; Ward, Nicholas D.; Sawakuchi, Henrique O.; Cunha, Alan C.; Richey, Jeffrey E.
Abstract: Estimations of the global carbon budget include a quantitative understanding of the evolving processes that occur along river-to-ocean gradients. However, high spatiotemporal resolution observations of these processes are limited. Here we present in situ measurements of the partial pressure of CO2 ( pC O2 ) made through the Amazon River plume (ARP) during different discharge seasons, from 2010 to 2012. We evaluated the spatiotemporal distribution of pC O2 using Soil Moisture and Ocean Salinity (SMOS) satellite observations for each hydrologic period in the ARP. Regression models were used to estimate pC O2 at the ARP for the period of 2010–2014. From these distributions we calculated sea-air gas exchange of CO2 between the plume waters and the atmosphere ( F co 2 sea ). Intra-annual variability of F co 2 sea was related to discharge at the river mouth and ocean currents as well as trade winds in the plume. Climatic events during the study period had a significant impact on the F co 2 sea . Including the plume area closer to the river mouth makes the ARP a net source of CO2 with an annual net sea-air flux of 8.6 ± 7.1 Tg C y −1 from 2011 to 2014. Graphical abstract: Image 1 Highlights: Remote sensing was used to evaluate air-sea CO2 exchange in the Amazon River plume. Plume CO2 fluxes varied by season and year, shifting between a net sink to source. The plume was a net source of CO2 to the atmosphere during rising water. The inner Amazon River plume had high CO2 fluxes compared to the outer plume. The plume is a net source of CO2 when the inner plume is included.